Risk and safety requirements for diagnostic and therapeutic procedures in allergology: World Allergy Organization Statement. Issue 1 (December 2016) - Kowalski, Marek; Ansotegui, Ignacio; Aberer, Werner; Al-Ahmad, Mona; Akdis, Mubeccel; Ballmer-Weber, Barbara; Beyer, Kirsten; Blanca, Miguel; Brown, Simon; Bunnag, Chaweewan; Hulett, Arnaldo; Castells, Mariana; et al.
Abstract One of the major concerns in the practice of allergy is related to the safety of procedures for the diagnosis and treatment of allergic disease. Management (diagnosis and treatment) of hypersensitivity disorders involves often intentional exposure to potentially allergenic substances (during skin testing), deliberate induction in the office of allergic symptoms to offending compounds (provocation tests) or intentional application of potentially dangerous substances (allergy vaccine) to sensitized patients. These situations may be associated with a significant risk of unwanted, excessive or even dangerous reactions, which in many instances cannot be completely avoided. However, adverse reactions can be minimized or even avoided if a physician is fully aware of potential risk and is prepared to appropriately handle the situation. Information on the risk of diagnostic and therapeutic procedures in allergic diseases has been accumulated in the medical literature for decades; however, except for allergen specific immunotherapy, it has never been presented in a systematic fashion. Up to now no single document addressed the risk of the most commonly used medical procedures in the allergy office nor attempted to present general requirements necessary to assure the safety of these procedures. Following review of available literature a group of allergy experts within the World Allergy Organization (WAO), representing various continents and areas of allergy expertise, presents this report on risk associated with diagnostic and therapeutic procedures in allergology and proposes a consensus on safety requirements for performing procedures in allergy offices. Optimal safety measures including appropriate location, type and required time of supervision, availability of safety equipment, access to specialized emergency services, etc. for various procedures have been recommended. This document should be useful for allergists with already established practices and experience as well as to other specialists taking care of patients with allergies.